2015
DOI: 10.1108/wjemsd-05-2015-0025
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability in start-up ventures: what founders say versus what they do

Abstract: Founders of start-up ventures today can benefit from implementing sustainability efforts to enhance their viability over the long term. But, do founders of start-up ventures regularly incorporate and reinforce sustainable business practices in their business models? An opinion survey of prospective business start-up founders, along with a content analysis of their business plans, is used to compare founders' views-"what they say"about sustainable business practices to their described business models-"what they… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
1
6
0
1
Order By: Relevance
“…There is no consensus definition of sustainability that remains an ill-defined term (Galpin & Hebard, 2015) with more than 70 different definitions (Lozano, 2008) being proposed by various studies (Barkemeyer et al, 2014;Owens & Legere, 2015;Habidin, Zubir, Fuzi, Latip, & Azma, 2015;Ratiu & Anderson, 2015), depending on how the sustainability is approached and perceived (Lozano, 2008;Barkemeyer et al, 2014;Owens & Legere, 2015). Even though the aim of sustainability is to secure intergenerational equity, its meaning yet remains elusive (Bansal & DesJardine, 2014).…”
mentioning
confidence: 99%
“…There is no consensus definition of sustainability that remains an ill-defined term (Galpin & Hebard, 2015) with more than 70 different definitions (Lozano, 2008) being proposed by various studies (Barkemeyer et al, 2014;Owens & Legere, 2015;Habidin, Zubir, Fuzi, Latip, & Azma, 2015;Ratiu & Anderson, 2015), depending on how the sustainability is approached and perceived (Lozano, 2008;Barkemeyer et al, 2014;Owens & Legere, 2015). Even though the aim of sustainability is to secure intergenerational equity, its meaning yet remains elusive (Bansal & DesJardine, 2014).…”
mentioning
confidence: 99%
“…À guisa de implicações, destaca-se a importância de se tratar sobre aspectos sustentáveis no ambiente de startups, já que acabam por fornecer diferenciais competitivos (BOCKEN et al, 2014). Além disso, a incorporação da sustentabilidade em startups acaba por ser algo interessante, já que novas empresas apresentam poucos ou nenhum processo ou procedimento organizacional estabelecido (GALPIN; HEBARD, 2015), o que facilita a formulação de estratégias sustentáveis.…”
Section: Considerações Finaisunclassified
“…It is not that they act irresponsibly; instead, their approach towards CSR is different (Soundararajan et al, 2018). Startups are initiating CSR activities to enhance the viability of their firms in the long run (Galpin & Hebard, 2015). The limited research on this topic found that most startups undertook sustainable practices only to differentiate themselves (Jenkins, 2009) by maximizing product range (Schick et al, 2002), by incorporating it into the core structure of the organization right from the beginning (Grayson & Hodges, 2017), new opportunities through innovation (Jenkins, 2009), risk and cost reduction (Schaltegger et al, 2012), customer loyalty (Iglesias et al, 2018), stakeholder satisfaction, and excellent financial performance (Ngai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%